[18F]FDG PET-MRI provides survival biomarkers in primary central nervous system lymphoma in the elderly: an ancillary study from the BLOCAGE trial of the LOC network - Rozenblum, Laura; Galanaud, Damien; Houillier, Caroline; Soussain, Carole; Baptiste, Amandine; Belin, Lisa; Edeline, Véronique; Naggara, Philippe; Soret, Marine; Causse-Lemercier, Valérie; Willems, Lise; Choquet, Sylvain; et al. (European journal of nuclear medicine and molecular imaging, 2023)
Primary central nervous system lymphoma (PCNSL) incidence is rising among elderly patients, presenting challenges due to poor prognosis and treatment-related toxicity risks. This study explores the potential of combining [18F]fluorodeoxyglucose ([18F]FDG) PET scans and multimodal MRI for improving management in elderly patients with de novo PCNSL. Immunocompetent patients over 60 years with de novo PCNSL were prospectively enrolled in a multicentric study between January 2016 and April 2021. Patients underwent brain [18F]FDG PET-MRI before receiving high-dose methotrexate-based chemotherapy. Relationships between extracted PET (metabolic tumor volume (MTV), sum of MTV for up to five lesions (sumMTV), metabolic imaging lymphoma aggressiveness score (MILAS)) and MRI parameters (tumor contrast-enhancement size, cerebral blood volume (CBV), cerebral blood flow (CBF), apparent diffusion coefficient (ADC)) and treatment response and outcomes were analyzed. Of 54 newly diagnosed diffuse large B-cell PCNSL patients, 52 had positive PET and MRI with highly [18F]FDG-avid and contrast-enhanced disease (SUVmax: 27.7 [22.8-36]). High [18F]FDG uptake and metabolic volume were significantly associated with low ADCmean values and high CBF at baseline. Among patients, 69% achieved an objective response at the end of induction therapy, while 17 were progressive. Higher cerebellar SUVmean and lower sumMTV at diagnosis were significant predictors of complete response: 6.4 [5.7-7.7] vs 5.4 [4.5-6.6] (p = 0.04) and 5.5 [2.1-13.3] vs 15.9 [4.2-19.5] (p = 0.01), respectively. Two-year overall survival (OS) was 71%, with a median progression-free survival (PFS) of 29.6 months and a median follow-up of 37 months. Larger tumor volumes on PET or enhanced T1-weighted MRI were significant predictors of poorer OS, while a high MILAS score at diagnosis was associated with early death (< 1 year). Baseline cerebellar metabolism and sumMTV may predict response to end of chemotherapy in PCNSL. Tumor volume and MILAS at baseline are strong prognostic factors.